Purification and characterization of thermostable serine alkaline protease from Geobacillus sp. DS3 isolated from Sikidang crater, Dieng plateau, Central Java, Indonesia - Sotharith Phon; Andriati Ningrum; Lucia Dhiantika Witasari (Universitas Gadjah Mada, 2022)
Thermostable proteases that optimally withstand the high‐temperature conditions of thermophilic bacteria could be produced and purified, which would be highly beneficial for use in industry. Geobacillus sp. is a thermophilic bacterium that can be found in various environmental conditions. The goal of this study was to isolate and characterize thermostable serine protease that had been produced by thermophilic Geobacillus sp. strain DS3. The proteolytic index was measured in a solid medium. The expression of protease was optimized by Geobacillus sp. DS3 at 50 °C for 18 h. Targeted protease was purified using ammonium sulfate (40‐60%) and DEAE Sephadex A‐25 resin. Using SDS‐PAGE, the molecular weight of the enzyme was predicted to be around 32 kDa. Purified thermostable protease was highly activated at 70 °C, pH 9.6 stable for 1 h, and inhibited by PMSF. Therefore, this enzyme is classified as a thermostable alkaline serine protease. Its kinetic study revealed specific activity of 0.41 U/mg (Vmax) and 0.25 mg/mL (KM). Overall, a thermostable alkaline serine protease from Geobacillus sp. DS3 showed high activity at high temperatures and alkaline pH, which is vital for application in industries such as leather processing and detergent formulation.